Associations of interpersonal and socioeconomic early life adversity dimensions with adolescents’ corticolimbic circuits, cognition, and mental health - Yumeng Yang; Tianjiao Kong; Ran Liu; Liang Luo (Translational Psychiatry)
Abstract Early life adversity (ELA) is highly prevalent and has significant detrimental effects on children’s brain development and behavioral outcomes. However, associations of threat, unpredictability, and deprivation in dimensional models of ELA with corticolimbic circuits were unclear. Previous studies have highlighted the effects of proximity, especially the distinctions between interpersonal and socioeconomic ELA, on children’s neurodevelopment. This study first examined the associations between multiple ELA categories (i.e., interpersonal threat, socioeconomic threat, interpersonal unpredictability, socioeconomic unpredictability, interpersonal deprivation, and socioeconomic deprivation) and the developmental changes in resting-state functional connectivity (rsFC) of the frontolimbic and temporal-limbic circuits implicated in cognition and psychopathology, using data from the Adolescent Brain Cognitive Development (ABCD) study, which included four measurements from baseline (mean ± SD age, 119.13 ± 7.51 months; 2815 females) to 3-year follow-up (N = 5885). Controlling for concurrent ELA categories, interpersonal unpredictability and socioeconomic deprivation were associated with accelerated development of rsFC between CON/RTN-amygdala/hippocampus (Cingulo-opercular Network, Retrosplenial Temporal Network). Compared to girls, boys’ corticolimbic circuits development was more sensitive to interpersonal threat. Changes in rsFC mediated the associations between interpersonal unpredictability/socioeconomic deprivation with decreased crystallized cognition, fluid cognition, and internalizing problems. Additionally, socioeconomic deprivation was associated with decreased crystallized cognition through interpersonal unpredictability and changes in rsFC between CON and bilateral amygdala/right hippocampus. This study emphasized interpersonal unpredictability and socioeconomic deprivation as key environmental factors affecting corticolimbic circuit development implicated in cognition and psychopathology. Stable family environments and enriched neighborhoods are crucial for supporting optimal neural and behavioral development in children and adolescents.